2010
DOI: 10.1194/jlr.m900274-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

HNF1α and SREBP2 are important regulators of NPC1L1 in human liver

Abstract: This article is available online at http://www.jlr.org target of the cholesterol-lowering drug ezetimibe ( 1, 2 ). Mice defi cient in NPC1L1 have ‫ف‬ 70% reduction in cholesterol absorption ( 1 ) and resistance to diet-induced hypercholesterolemia ( 3 ). NPC1L1 is widely expressed in many human tissues, with the highest expression in small intestine and in the liver ( 3, 4 ). In mice and rats, npc1l1 is predominantly expressed in the small intestine, whereas all others tissues showed expression levels <10% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Moreover, they accumulated less cholesterol in both their bile (7.36 ± 0.58 mol/ml versus 11.1 ± 1.01 mol/ml, P < 0.05) and liver (79% lower, P < 0.01) than the control mice receiving the same cholesterol-enriched diet. Although these results support the premise that human NPC1L1 variants could modulate LDL-C levels by directly affecting NPC1L1 transcript numbers, their translatability, or both, other data reveal a disconnect between determinants of NPC1L1 gene expression ( 55,56 ) and NPC1L1 protein levels ( 57 ). Thus, in a crossover study involving 22 men with modestly raised LDL-C (i.e., >50 th percentile value for their age (38.1 ± 9.8 years), it was found that atorvastatin (12 weeks, 40 mg/day or placebo) increased intestinal NPC1L1 expression by 18.7% ( P = 0.03), as judged by RNA concentrations in duodenum biopsy samples.…”
mentioning
confidence: 46%
“…Moreover, they accumulated less cholesterol in both their bile (7.36 ± 0.58 mol/ml versus 11.1 ± 1.01 mol/ml, P < 0.05) and liver (79% lower, P < 0.01) than the control mice receiving the same cholesterol-enriched diet. Although these results support the premise that human NPC1L1 variants could modulate LDL-C levels by directly affecting NPC1L1 transcript numbers, their translatability, or both, other data reveal a disconnect between determinants of NPC1L1 gene expression ( 55,56 ) and NPC1L1 protein levels ( 57 ). Thus, in a crossover study involving 22 men with modestly raised LDL-C (i.e., >50 th percentile value for their age (38.1 ± 9.8 years), it was found that atorvastatin (12 weeks, 40 mg/day or placebo) increased intestinal NPC1L1 expression by 18.7% ( P = 0.03), as judged by RNA concentrations in duodenum biopsy samples.…”
mentioning
confidence: 46%
“…This suggests that the up-regulation of proteins involved in the assembly and secretion of TAG-rich lipoproteins may contribute to an increase in the serum concentration of TAGs after lipectomy. Taking into account the results of previous studies in which HNF1α and HNF4α were shown to be transcriptional activators of Mttp and Apob genes [38,39], and our hereby presented findings, we postulate that these hepatocyte nuclear factors (HNFs) might contribute to the hypertriglyceridemia observed in lipectomized rats. This is consistent with the results of a recent study in which lipectomized rats presented with higher concentrations of circulating TAGs and higher liver levels of HNF4α mRNA than the sham-operated controls [13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data reported previously, indicating that Mttp , ApoB , Fasn and Srebf-1 are target genes for HNFs [38,39,48] and the results presented in this paper, we propose a mechanistic scheme showing how HNFs may affect circulating TAG concentrations in lipectomy rats (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Sterol-responsive element-binding protein-2 (SREBP2) activates the transcription of the LDLR gene and all of the genes that encode cholesterol synthesis enzymes (13). In addition, the NPC1L1 gene has been shown to be activated by SREBP2 (26). Higher levels of SREBP2 mRNA (2.8-fold) in low responders were associated with higher levels of LDLR and NPC1L1 mRNAs, except HMGCR mRNA, in low responders.…”
Section: Differences In Expression Of Cholesterol Metabolism Genesmentioning
confidence: 90%